Obliquity disruption and Antarctic ice sheet dynamics over a 2.4-Myr astronomical grand cycle - Sullivan,NB; Meyers,SR; Levy,RH; Mckay,RM; van,de Flierdt T; Marschalek,J; Perotti,M; Zureli,L; Talarico,F; Harwood,D; De,Santis L; Florindo,F; et al. (Science Advances, 2025)
Marine δ18O data reveal astronomical forcing of the climate and cryosphere during the Miocene, when atmospheric Pco2 was on par with emissions scenarios over the next century. This inspired hypotheses for how Milankovitch cycles, ice-ocean interactions, and greenhouse gases influence ice volume. Mass balance controls for marine and terrestrial ice sheets differ, and proxy data collected far from Antarctica provide valuable but limited insight into regional processes. We evaluate clast abundance data from Antarctic marine sedimentary records, observing a strong signal of eccentricity and precession coincident with a terrestrial ice sheet and a clear obliquity signal at the margins of a marine ice sheet. These analyses are integrated with a synthesis of proxy data, and we argue that high variance in obliquity forcing (mediated and enhanced by the ocean and atmosphere) can inhibit ice sheet growth, even when insolation forcing is conducive to glaciation. This “obliquity disruption” explains cryosphere variability before the existence of large northern hemisphere ice sheets.